On the margins of standard compounding: the phrasal compound adjective playing with the norms - Jean MISSUD (E-REA)
This article investigates the boundary between acceptable and unacceptable phrasal compound adjectives in pre-nominal position. Considered marginal by many existing studies, the phrasal compound is often said to be non-standard; phrasal compounding consists of the linking of several lexical elements linked together, usually by multiple hyphenation.First, this article will explore the ways in which this multi-faceted element is defined in the existing literature; I will seek to determine if the phrasal compound could potentially become part and parcel of the existing definitions and typologies of compounding. Finally, I will consider whether phrasal compound adjectives are still considered marginal when they occur in works of literature.